Faktor Risiko Kejadian Demam Berdarah Dengue di Indonesia - Sulfi Udi; Tri Yunis Miko Wahyono (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Dengue hemorrhagic fever is a health problem that is often experienced by tropical and subtropical countries throughout the world. Indonesia is a country with the greatest risk of dengue hemorrhagic fever in the world. This study aims to determine the risk factors for DHF in Indonesia. This study is a literature review involving the ScienceDirect and Google Scholar databases. The keywords used are “Risk Factor” of “Dengue Hemorrhagic Fever” in Indonesia and “Factor” of “Dengue Hemorrhagic Fever” in Indonesia, with inclusion criteria: articles 2021-2022; published between September 2021 to September 2022; speak Indonesian or English; original research; available in full text; discusses the causes of dengue hemorrhagic fever. Of the 8 articles that met the criteria, it was found that the risk factors for dengue hemorrhagic fever in Indonesia were: climate, environmental sanitation, knowledge and attitudes, 3M plus behavior, individual characteristics, and components of vulnerability.Keywords: Aedes aegypti; dengue hemorrhagic fever; risk factor ABSTRAK Demam berdarah dengue merupakan masalah kesehatan yang sering dialami oleh negara-negara tropis maupun subtropis di seluruh dunia. Indonesia merupakan negara dengan risiko kejadian demam berdarah dengue terbesar di dunia. Studi ini bertujuan untuk mengetahui faktor-faktor risiko kejadian DBD di Indonesia. Studi ini merupakan kajian literatur yang melibatkan database ScienceDirect dan Google Schoolar. Kata kunci yang digunakan yaitu “Risk Factor” of “Dengue Hemorrhagic Fever” in Indonesia dan “Factor” of “Dengue Hemorrhagic Fever” in Indonesia, dengan kriteria inklusi: artikel tahun 2021-2022; dipublikasikan dalam rentang September 2021 hingga September 2022; berbahasa Indonesia atau Inggris; original research; tersedia dalam full text; membahas faktor-faktor penyebab demam berdarah dengue. Dari 8 artikel yang memenuhi kriteria ditemukan bahwa faktor risiko kejadian demam berdarah dengue di Indonesia yaitu: iklim, sanitasi lingkungan, pengetahuan dan sikap, perilaku 3M plus, karakteristik individu, serta komponen kerentanan.Kata kunci: Aedes aegypti; demam berdarah dengue; faktor risiko